Pension wealth and intergenerational succession in family businesses - Kimhi, Ayal (2015)
lntergenerational transfers are extremely important in family businesses, because of the economic advantages of passing the business to the next generation as a 'going concern'. In order to pass the business as a 'going concern' it is necessary for the operators and the successors to work together for a specified period. This intergenerational cooperation allows the entrepreneurial family to utilize the benefits of within-family implicit old-age security arrangements. We suggest a method to calculate the present value of these benefits, denoted as 'pension wealth'. Intra-family old-age security arrangements also pose financial risks on successors that may offset the benefit the household attains from the implicit annuity arrangement. We illustrate the usefulness of this framework with data from Israeli family farms.